Forecasting innovative development of infrastructure providing services to agriculture - KHAMRAEVA, SAYYORA NASIMOVNA (The journal of contemporary issues in business and government, 2021)
The article is devoted to the analysis of the innovative development of agriculture and its infrastructure services through mathematical materials and the development of prospects. The results of the multifactor econometric model were developed using statistical data and Eviews software. According to the results of the obtained econometric model, the influence of factors on changes in the volume of infrastructure services provided to agriculture was determined. Also, on the basis of the developed trend models, the forecast parameters of the volume of agricultural infrastructure services, gross agricultural output, the number of machine-tractor parks and zoo- veterinary stations until 2023 were determined.